The Long-term Impact of War on Health and Well-being in Northern Vietnam: Some Glimpses from a Recent Survey - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2011)
War is considered one of the most intransigent obstacles to development; yet, the long-run effects of war on individual health have rarely been examined in the context of developing countries. Based on unique data recently collected as a pilot follow-up to the Vietnam Longitudinal Survey, this study examines health status of northern Vietnamese war cohorts (those who entered adulthood during the Vietnam War and now represent Vietnam’s older-adult population). To ascertain whether and how war impacts old-age physical and mental health, we compare multi-dimensional measures of health among war survivors, including civilians, combatants, noncombatants, and nonveterans involved in militia ctivities. Multivariate results suggest that despite prolonged exposure to war and trauma, combat and noncombat veterans are not significantly different from their civilian counterparts in terms of self-rated, functional, and mental health in older adult years. That we do not observe war’s adverse effects for veterans might be explained by the encompassing extent of war in northern Vietnamese society.